Рedagogical artistry teacher as part of its professional competence in preparing penitentiary staff - Третяк, О. С. (Pedagogy of Higher and Secondary Education, 2012)
Tretiak А. Рedagogical artistry teacher as part of its professional competence in preparing penitentiary staff. The article deals with the components artistry teacher and outlines the rules that allow the teacher to effectively influence the learning environment. While allocated to training classes, teachers have the ability to emotions, body, facial expressions, voice, motivate students to acquire skills and experience.